DEVELOPMENT AND CHALLENGES OF SHARIA BANKING IN INDONESIA IN THE GLOBAL FINANCIAL CONTEXT - Yanti (Institut Agama Islam Sumatera Barat), Novi; (Institut Agama Islam Sumatera Barat), Syamsurizal; Bakar (Islamic Business School, College of Business, Universiti Utara Malaysia), Nashirah Abu; Wandi (Institut Agama Islam Sumatera Barat), Joni Indra; (Institut Agama Islam Sumatera Barat), Andrianto (Universitas Muhammadiyah Lampung, 2024)
Islamic banking has become a crucial sector within the global financial system, including in Indonesia. This research explores the development and challenges faced by Islamic banking in Indonesia within the context of the global financial landscape. The study employs secondary data analysis, literature review, and interviews with policy makers and Islamic banking practitioners. The growth of Islamic banking in Indonesia has shown significant progress in recent years. The primary driving factors behind this growth are the increasing public awareness of Sharia principles and government support in the form of regulatory frameworks. Islamic banks have successfully attracted numerous individual and corporate clients seeking Sharia-compliant financial solutions. However, several challenges confront Islamic banking in Indonesia in the face of the global financial context. First and foremost, intensifying competition with conventional banks is a major challenge. Conventional banks have begun offering Sharia-compliant products, intensifying the competition for market share. Second, gaining access to global Islamic financial products is a significant challenge. The evolving global financial market offers significant opportunities for Islamic banking in Indonesia to participate, but the challenge lies in understanding and accessing Sharia-compliant global financial products. Third, developing a skilled and competent workforce in the field of Islamic banking is another challenge. To cope with the complexities of the global financial market, Islamic banks need to have a workforce that is both competent and proficient. This research also discusses the efforts made by Islamic banks in Indonesia to address these challenges, including product innovation, international collaborations, and enhancing the quality of human resources.